2000
DOI: 10.1021/ma000682a
|View full text |Cite
|
Sign up to set email alerts
|

Bond Scission in a Perfect Polyethylene Chain and the Consequences for the Ultimate Strength

Abstract: We present ab initio calculations concerning the bond scission rate in a polyethylene chain. The energy barrier for scission is calculated both by using an effective potential scheme based on ab initio data and from the ab initio transition state itself. In the latter case the prefactor for scission is calculated. In both methods the relaxation of the polymer chain is taken into account, leading to a strong strain dependence of the energy barrier. The two schemes agree quantitatively. The barrier is reduced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
0
31
1
Order By: Relevance
“…However, this value does not differ too much from the results of the more advanced modelling by J.C.L. Hageman et al [4], who found a value of about 300GPa at room temperature. The highest experimental value was about 280 GPa at 77K.…”
Section: E=11tpacontrasting
confidence: 64%
See 1 more Smart Citation
“…However, this value does not differ too much from the results of the more advanced modelling by J.C.L. Hageman et al [4], who found a value of about 300GPa at room temperature. The highest experimental value was about 280 GPa at 77K.…”
Section: E=11tpacontrasting
confidence: 64%
“…These predict lower values. An example is the model by J. C. L. Hageman et al [4], which predicts an ultimate strength of about 18GPa at room temperature. Ultra drawn polyethylene fibres are indeed very strong.…”
Section: E=11tpamentioning
confidence: 99%
“…In addition, many commercial and open-source computational codes are available for QM and DFT calculations [394,395]. Some of the applications of firstprinciple methods, mainly DFT, to PE models are conformational and mechanical properties of single chain models [240,245,246,248,[396][397][398][399][400][401][402][403][404][405][406][407][408], equilibrium unit cell, [239, 245-249, 396, 409], electronic properties [238,401,402,407,[409][410][411][412][413][414][415][416][417], infrared and/or Raman spectra of the crystal state [243,246,263,415,418], inelastic neutron scattering spectra [245,419], and Shock Hugoniot studies of PE crystals (studies of the material's behaviour under extreme conditions) [420,421].…”
Section: Quantum Scale Ab Initio Quantum (Qm) and Density Functionalmentioning
confidence: 99%
“…Zhurkov and co-workers [9] have proposed long ago that mechanical breakdown was a kinetic bond scission process and in support of their affirmation they detected free radicals during the aging and breakdown processes. Assuming that strained bonds might relax during deformation, results in a C-C bonds strength value reduced to 30-40% of its original value [10].…”
Section: The Activation Energy and The Strength Of C-c Bondsmentioning
confidence: 99%